Hematological and Performance Variables of Male Broiler Chickens Fed with Moringa oleifera Extract and Probiotic in Drinking Water - Yulianto, A. B.; Lamid, M.; Lokapirnasari, W. P.; Al-Arif, M. A.; Sherasiya, A.; Marbun, T. D.; Khairullah, A. R.; Kurniawan, S. C.; Hasib, A.; Silaen, O. S. M.; Rehman, S.; Ayuti, S. R. (Faculty of Animal Science, IPB University, 2024)
Moringa oleifera is a potential plant that can be used to improve immunity, the gut health of broiler chickens, and reduce the number of pathogens in the intestine. Probiotics are non-pathogenic microbes that can balance the microflora in the digestive tract and improve poultry production performance. The objective of this study was to demonstrate the impact of adding probiotic Lactobacillus sp. and M. oleifera extract to broiler feed. In this study, a factorial, completely randomized design was used. This research used 900 animals, which were divided into two factors: the first factor was the dose of M. oleifera (0%, 1%, and 2%) and the second factor was the dose of probiotics (0%, 1 %, and 2%). The treatment was 9 (3 x 3 factorial design), with each consisting of 10 replications and each replication consisting of 10 chickens. M. oleifera extract and probiotics were supplemented in drinking water during the 5-week experimental period. Ad libitum supplies of food and drink were provided. The results revealed that there was an interaction (p<0.05) between the doses of M. oleifera extract and probiotic on leucocytes, monocytes, granulocytes, thrombocytes, and hematocrit when M. oleifera extract and probiotics were added. There was no interaction between the doses of M. oleifera extract and probiotics on the levels of lymphocytes, hemoglobin, and erythrocytes, but all blood profile values were within the normal range. The feed intake, feed conversion ratio, and daily body weight gain showed significant differences (p<0.05) that increased between treatments. It could be concluded that using M. oleifera extract and Lactobacillus sp probiotics as feed additives did not alter the normal blood profile values and could increase the performance of male broiler chickens and income over feed cost (IOFC).